2015
DOI: 10.1186/s12882-015-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury molecule-1 expression in human kidney transplants with interstitial fibrosis and tubular atrophy

Abstract: BackgroundKidney injury molecule-1 (KIM-1) is expressed in tubular epithelial cells after injury and may have a role in the development of renal graft fibrosis. In this study we evaluated the molecular and protein expressions of KIM-1 in dysfunctional allografts and also mRNA KIM-1 expression in urine as potential biomarkers of graft fibrosis.MethodsProtein and mRNA levels in renal tissue and urinary sediment cells of 69 kidney transplant recipients that undertook for-cause graft biopsies were evaluated by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A significant correlation between KIM-1 gene expression in samples of urine and tissue cells was found (p < 0.01). Nogare et al 52 also found that KIM-1 protein expression was increased in biopsies with interstitial fibrosis and tubule atrophy, compared with biopsies showing acute calcineurin inhibitor nephrotoxicity.…”
Section: Kim-1 and Kidney Transplantmentioning
confidence: 92%
“…A significant correlation between KIM-1 gene expression in samples of urine and tissue cells was found (p < 0.01). Nogare et al 52 also found that KIM-1 protein expression was increased in biopsies with interstitial fibrosis and tubule atrophy, compared with biopsies showing acute calcineurin inhibitor nephrotoxicity.…”
Section: Kim-1 and Kidney Transplantmentioning
confidence: 92%
“…A clinical study showed that urinary KIM-1 could predict the development of graft loss after kidney transplantation [122]. Therefore, KIM-1 has been consistently demonstrated to be an early indicator of kidney injury and is considered a highly sensitive and specific urinary biomarker for monitoring drug-induced kidney injury [123][124][125][126].…”
Section: Urinary Biomarkers and Nephrotoxicitymentioning
confidence: 99%
“…Studies have revealed that urinary KIM-1 protein concentrations are significantly higher in patients with AKI [123,124], but increased KIM-1 expression can also be an early marker for identifying renal tubular damage. Nogare et al [125] have reported that KIM-1 protein expression is increased in biopsies with interstitial fibrosis and tubular atrophy, implying that KIM-1 can serve as a biomarker of chronic kidney injury (CKI) induced by CNIs. Thus, KIM-1 expression is significantly related to kidney function, which makes KIM-1 a sensitive and specific marker of both AKI and CKI.…”
Section: Urinary Biomarkers and Nephrotoxicitymentioning
confidence: 99%
“…In the past years, besides NGAL, several AKI and DGF biomarkers have been extensively investigated, including urinary KIM‐1, IL‐18, heat shock protein 72 (uHsp72), L‐FABP, calprotectin, CXCL9, CXCL10, CCL2, IL‐18, cystatin C, T‐cell immunoglobulin, and mucin domain‐3 (Tim‐3), tissue inhibitor of metalloproteinase 2 (TIMP‐2), insulin‐like growth factor‐binding protein 7 (IGFBP‐7) 57, 58, 59, 60, 61, 62, 63.…”
Section: Ngal and Other Candidate Biomarkers In Kidney Transplant Setmentioning
confidence: 99%